2010
DOI: 10.1042/bj20100232
|View full text |Cite
|
Sign up to set email alerts
|

O-Acetylation of sialic acid on Group BStreptococcusinhibits neutrophil suppression and virulence

Abstract: Synopsis Group B Streptococcus (GBS) requires capsular sialic acid (Sia) for virulence and partially modifies this sugar by O-acetylation. We describe serotype specific patterns of GBS Sia O-acetylation that can be manipulated by genetic and biochemical means. In vitro and in vivo assays demonstrate this subtle modification attenuates GBS Sia-mediated neutrophil suppression and animal virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 46 publications
0
45
0
Order By: Relevance
“…Site-specific mutation of a GBS O-acetylesterase has facilitated genetic control of O-acetylation levels (here referred to as GBS-hiOAc [80% of total surface sialic acids modified] and GBS-loOAc [ϳ2% of total surface sialic acids modified]) (29). Previous studies have shown that O-acetylation does not impact GBS complement evasion but does impede sialic acid-Siglec-9 engagement and thus attenuates bacterial evasion of human neutrophils (57,58). Murine neutrophils express a homolog of human Siglec-9 called Siglec-E.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Site-specific mutation of a GBS O-acetylesterase has facilitated genetic control of O-acetylation levels (here referred to as GBS-hiOAc [80% of total surface sialic acids modified] and GBS-loOAc [ϳ2% of total surface sialic acids modified]) (29). Previous studies have shown that O-acetylation does not impact GBS complement evasion but does impede sialic acid-Siglec-9 engagement and thus attenuates bacterial evasion of human neutrophils (57,58). Murine neutrophils express a homolog of human Siglec-9 called Siglec-E.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously characterized a naturally occurring GBS capsule modification (sialic acid Oacetylation), which is expressed at low to moderate levels in all tested serotypes (30,58). Site-specific mutation of a GBS O-acetylesterase has facilitated genetic control of O-acetylation levels (here referred to as GBS-hiOAc [80% of total surface sialic acids modified] and GBS-loOAc [ϳ2% of total surface sialic acids modified]) (29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, acetylation can alter the molecular conformation (41) and increase the viscosity (42) of polysaccharides. Acetylation can also create and/or alter epitopes targeted by immune molecules, such as antibodies (16,43), lectins (10,44), and enzymes (45). Further, acetylation increases resistance to hypochlorite, an oxidizing agent produced in neutrophils (46).…”
Section: Discussionmentioning
confidence: 99%